The Russia-Ukraine grain agreement: What is at stake? - Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
On July 22, 2022, Ukraine and Russia reached an agreement to allow exports of grain and other agricultural products to resume from selected Ukraine Black Sea ports after months of Russian blockade. The agreement comes at a time when storage capacity is reaching its limits, with much of the 2022 wheat harvest and the approximately 20 million metric tons of grains and oilseeds harvested in 2021 remaining in storage — unable to ship because of the blockade. The deal, brokered by Türkiye and the United Nations, has been widely praised; resuming Ukrainian trade should help ease market prices, consolidating the reductions seen in recent weeks and helping to bring prices back to the pre-COVID-19 levels of 2020. Indeed, wheat prices had already fallen to their pre-invasion level by July 1, while corn prices returned to pre-war levels by July 17. Still, prices for both cereals remain 50% higher than 30 months ago [July 2020].